Lower Angara Region – Analysis of the Paleolithic Complex «Irkineyevo. Site Yelchimo-3» (2013 research) - Razgildeeva Irina I.; Reshetova Svetlana A.; Klementiev Aleksey M.; Grevtsov Yuriy A. (Поволжская археология, 2020)
The Research 2013 of the multi-layered archaeological settlement “Irkineyevo. Site Yelchimo-3” allowed to discover a stratified complex of the Upper Paleolithic site, aged 12–11 thousand years ago, in the Northern Angara region. The geological position of the cultural horizon connected with a complex of alluvial soils in a middle part of deposits of the first terrace rising above the floodplain of the Angara River, the preservation of archaeological materials in situ context, the zoo-archaeological collection in combination with the stone inventory provided highly informative data. The goals of research included the reconstruction of paleoenvironment and life support ways of the ancients in conditions of a point archaeological object. Spatial analysis showed the localization of cultural remains reflecting a cycle of multi-event activity in a hunting camp. The level of food life support is characterized by the species composition of the fauna. With the dominance of the reindeer remains the bones of birds, wolfs, roe deer and primeval bison were met here. The activity carried out on the site included the organization of the temporary camp, arrangement of a fire and resting place, food preparation and consumption, butchering of animals and preparation them to transportation. The main task of the inhabitants of the site was meat preparation for the future. Raw stone processing was situational in nature. Among the knapping products: wedge-shaped cores, flakes; blade-like flakes and micro blade-like flakes. The collection of tools consists of scraping-cutting tools (including retouched flakes), pebbly hammer-stones, and a piece of the red deer point. The analysis fulfilled by the authors indicated that the episode of the hunting camp functioning had a single-shot character during the autumnwinter period. The duration has been determined by the ratio of the number of harvested animals and the acts of hunting activity.